2011
DOI: 10.1007/s00414-011-0580-7
|View full text |Cite
|
Sign up to set email alerts
|

The examination and identification of bite marks in foods using 3D scanning and 3D comparison methods

Abstract: Bite mark analysis offers the opportunity to identify the biter based on the individual characteristics of the dentitions. Normally, the main focus is on analysing bite mark injuries on human bodies, but also, bite marks in food may play an important role in the forensic investigation of a crime. This study presents a comparison of simulated bite marks in different kinds of food with the dentitions of the presumed biter. Bite marks were produced by six adults in slices of buttered bread, apples, different kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
16

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 23 publications
1
31
0
16
Order By: Relevance
“…The skeletal models were fused with 3D dentition using the iterative closest point (ICP) algorithm to generate virtual maxillary and mandibular dentition models and the maxillomandibular complex (MMC) model. The ICP algorithm minimizing the difference between the points of two 3D shapes has been commonly used for registration of different 3D models (Besl and Mckay, 1992;Nkenke et al, 2004;Sohmura et al, 2004;Uechi et al, 2006;Blackwell et al, 2007;Naether et al, 2012;Uechi et al, 2015). The absolute error of the 3D registration ranged from 0.21 to 0.31 mm in our study, which was comparable to those in previous studies (Nkenke et al, 2004;Uechi et al, 2006Uechi et al, , 2015.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The skeletal models were fused with 3D dentition using the iterative closest point (ICP) algorithm to generate virtual maxillary and mandibular dentition models and the maxillomandibular complex (MMC) model. The ICP algorithm minimizing the difference between the points of two 3D shapes has been commonly used for registration of different 3D models (Besl and Mckay, 1992;Nkenke et al, 2004;Sohmura et al, 2004;Uechi et al, 2006;Blackwell et al, 2007;Naether et al, 2012;Uechi et al, 2015). The absolute error of the 3D registration ranged from 0.21 to 0.31 mm in our study, which was comparable to those in previous studies (Nkenke et al, 2004;Uechi et al, 2006Uechi et al, , 2015.…”
Section: Discussionsupporting
confidence: 84%
“…Optically scanned dentition provided higher resolution and accuracy than CT imaging, as well as an increase in the accuracy of the physical models, regardless of their type (Frisardi et al, 2011). Therefore, combining the CT image with optically scanned dentition provided a highquality image of the tooth surface and enabled the use of anatomical landmarks on the skeletal model in the planning stage (Nkenke et al, 2004;Sohmura et al, 2004;Blackwell et al, 2007;Naether et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…By creating similar models, the suspected injury-inflicting instruments, crime scenes or dental imprints (Naether et al 2012) can also be matched to the body surface injuries. This technique can be applied very effectively to traffic fatalities Postmortem needle biopsy is a feasible method of tissue sampling (Filograna et al 2012).…”
Section: Postmortem Needle Biopsymentioning
confidence: 99%
“…. The validation of these techniques indicated that the best outcomes for bitemark analysis probably result from the 3D comparison of the dental morphology 21,22 . In this context, the present research was developed to test the ability of available software packages to compare the morphology of 3D laser scanned dentition.…”
Section: Methodsmentioning
confidence: 99%